Current and future daily temperature fluctuations make a pesticide more toxic: Contrasting effects on life history and physiology. (May 2019) - Verheyen, Julie; Stoks, Robby
Abstract: There is increasing concern that climate change may make organisms more sensitive to chemical pollution. Many pesticides are indeed more toxic at higher mean temperatures. Yet, we know next to nothing about the effect of another key component of climate change, the increase of daily temperature fluctuations (DTFs), on pesticide toxicity. Therefore, we tested the effect of the pesticide chlorpyrifos under different levels of DTF (constant = 0 °C, low = 5 °C (current maximum level) and high = 10 °C (predicted maximum level under global warming)) around the same mean temperature on key life history and physiological traits of Ischnura elegans damselfly larvae in a common-garden experiment. At all levels of DTF, chlorpyrifos exposure was stressful: it reduced energy storage (fat content) and the activity of its target enzyme acetylcholinesterase, while it increased the activity of the detoxification enzyme cytochrome P450 monooxygenase. Notably, chlorpyrifos did not cause mortality or reduced growth rate at the constant temperature (0 °C DTF), yet increased mortality 6x and reduced growth rate with ca. 115% in the presence of DTF. This indicates that daily short-term exposures to higher temperatures can increase pesticide toxicity. Our data suggest that when 5 °C DTF will become more common in the studied high-latitude populations, this will increase the toxicity of CPF, and that a further increase from 5° DTF to 10 °C DTF may not result in a further increase of pesticide toxicity. Our results highlight the biological importance of including daily temperature fluctuations in ecological risk assessment of pesticides and as an extra dimension in the climate-induced toxicant sensitivity concept. Graphical abstract: Image 1 Highlights: Daily temperature fluctuations (DTFs) increased chlorpyrifos toxicity. Chlorpyrifos only induced mortality and reduced growth rate in the presence of DTFs. Chlorpyrifos did not affect life history when the temperature was kept constant. Current and future DTF increased toxicity to the same extent. Abstract : Chlorpyrifos only induced mortality and reduced growth rate in the presence of daily temperature fluctuations and not when the temperature was kept constant.